Peran Guru Bimbingan Konseling dalam Pelaksanaan Bimbingan dan Konseling serta Mengatasi Kenakalan Siswa - Lutfiana, Anti; Mustofa, Riski Ali (Program Studi Bimbingan dan Konseling Islam, 2023)
Guidance and counseling services in schools are an effort to help students in learning activities, as well as career planning and development. Guidance and counseling services facilitate the development of individual, group, and classical learners. This service also helps overcome weaknesses and obstacles and problems faced by students. This research was conducted at SMP IT Insan Mulia Kotagajah. This study aims to determine the role of BK teachers in implementing counseling guidance programs and overcoming student delinquency at SMP IT Insan Mulia Kotagajah. The type of research used is qualitative with descriptive methods, the data collection techniques we use are observation, interviews and documentation. Based on the results of this study, it was concluded that the implementation of the guidance and counseling program at SMP IT Insan Mulia Kotagajah had run well. This happened because of the cooperation between BK teachers, school principals, teachers of other subjects and parents. The role of BK teachers in overcoming problem students is that students are given advice, guidance, assistance, and directing, as well as giving warnings. While the efforts that have been made are incidental efforts.